GC and Repeats Profiling along Chromosomes-The Future of Fish Compositional Cytogenomics - Matoulek, Dominik; Borůvková, Veronika; Ocalewicz, Konrad; Symonová, Radka (Genes, 2020)
The study of fish cytogenetics has been impeded by the inability to produce G-bands that could assign chromosomes to their homologous pairs. Thus, the majority of karyotypes published have been estimated based on morphological similarities of chromosomes. The reason why chromosome G-banding does not work in fish remains elusive. However, the recent increase in the number of fish genomes assembled to the chromosome level provides a way to analyse this issue. We have developed a Python tool to visualize and quantify GC percentage (GC%) of both repeats and unique DNA along chromosomes using a non-overlapping sliding window approach. Our tool profiles GC% and simultaneously plots the proportion of repeats (rep%) in a color scale (or vice versa). Hence, it is possible to assess the contribution of repeats to the total GC%. The main differences are the GC% of repeats homogenizing the overall GC% along fish chromosomes and a greater range of GC% scattered along fish chromosomes. This may explain the inability to produce G-banding in fish. We also show an occasional banding pattern along the chromosomes in some fish that probably cannot be detected with traditional qualitative cytogenetic methods.
Keywords: Software; software; tandemové repetitivní sekvence; kočky; repeats organization; ryby; zastoupení bazí; Tandem Repeat Sequences; fish cytogenetics; genom; chromosome banding; Gorilla gorilla; AT/GC heterogeneity; Genome; zvířata; Base Composition; pruhování chromozomů; Fishes; GC-profile; Chromosome Mapping; Chromosome Banding; karyotypizace; mapování chromozomů; Animals; Cats; Karyotyping